General Strategy
Break down what you need to prove according to the introduction rule. This is always possible for conjunction and implication. For a disjunction "$A \lor B$", it may not be possible because sometimes you can prove neither "$A$" nor "$B$", in which case you need to go by contradiction, which is to assume $\neg ( A \lor B )$ and obtain a contradiction, from which you can obtain $\neg \neg ( A \lor B )$ without any assumption and then use double negation elimination. Under the assumption, you still want to prove something of the form "$A \lor B$" but this time it is possible. First assume $A$ and obtain a trivial contradiction. So you can conclude $\neg A$ and proceed.
Solution (Fitch-style natural deduction)
$\def\imp{\rightarrow}$
If $( \neg p \land r ) \imp ( q \lor s )$:
If $\neg ( ( r \imp p ) \lor ( \neg s \imp q ) )$:
If $r \imp p$:
$( r \imp p ) \lor ( \neg s \imp q )$.
Contradiction.
$\neg ( r \imp p )$.
If $r$:
If $\neg p$:
$\neg p \land r$.
$q \lor s$.
If $\neg s$:
If $\neg q$:
If $q$:
Contradiction.
If $s$:
Contradiction.
Contradiction.
$\neg \neg q$.
$q$.
$\neg s \imp q$.
$( r \imp p ) \lor ( \neg s \imp q )$.
Contradiction.
$\neg \neg p$.
$p$.
$r \imp p$.
Contradiction.
$\neg \neg ( ( r \imp p ) \lor ( \neg s \imp q ) )$.
$( r \imp p ) \lor ( \neg s \imp q )$.
$( ( \neg p \land r ) \imp ( q \lor s ) ) \imp ( ( r \imp p ) \lor ( \neg s \imp q ) )$.